Impact of Barriers Encountered by Students with Disabilities on their Learning Experiences in Higher Education Institutions - Ambati, Nageswara Rao (JOURNAL OF INDIAN EDUCATION, 2017)
The present study is exploratory in nature. The paper aims to understand the barriers encountered by students with disabilities and their impact on the learning experiences of these students at higher education institutions. The study was conducted in the erstwhile State of Andhra Pradesh (now, bifurcated into Andhra Pradesh and Telangana). For this study, firstly, we selected three universities from different parts of Andhra Pradesh by using purposive sampling. Secondly, we interviewed 100 students with disabilities from selected universities by using snowball sampling. The mixed method approach, i.e., both quantitative and qualitative data analysis were employed in this study, and in most cases, the quotes of narratives for each theme were maintained and used extensively. The findings of the paper covered physical, academic and attitudinal barriers faced by the students with disabilities and their impact on the learning experiences of these students in obtaining higher education. Overall, these findings highlighted the inherent limitations in the current institutional arrangements on the basis of students, their parents, the attitude of university management and staff because these factors affected the learning experiences of the differently abled students in higher education institutions. A comprehensive access service is required for addressing the needs of these students, which should become an integral part of the institutions.